Technological adoption and trends in health sciences teaching, learning, and practice - Marcos-Pablos, Samuel, 1980-; Juanes-Mendez, Juan Antonio, 1959- (Advances in medical education, research, and ethics (AMERE) book series., 2022)
"This book can serve two purposes, one for developers of medical technologies to broaden their perspective for the creation of future medical technologies and applications, and the other for practitioners and medical educators to gain insight into emerging technological research within the health sciences"--